Feed Milling Industries Resilience amid COVID-19 in Nigeria - Adio Matthew Olufemi; Olarinde Luke Oyesola Oyesola; Ajetunmobi Oyepeju Abosede; Ayeni Matthew Durojaiye; Asake Sarah Adeola (Indonesian Journal of Business and Entrepreneurship Research, 2024)
This study analyzed the resilience strategies for small-scale feed milling industries, learning from the COVID-19 pandemic in Ekiti State, Nigeria. 215 small scale feed mills industries were selected by multistage sampling procedure. Descriptive statistics, gross margin and regression analysis were used for the analysis of data collected. Results revealed that the mean age for the respondents was 40.45 year. In addition, 91.58% of the feed millers were married while 8.42% were single with a mean household size of 6. 13 years was the mean number of years spent in school. With respect to experience, the respondents had 11 years of feed milling experience. Gross margin results indicated that income after COVID-19 is more than during the COVID-19 showing an N168,330.00 significant (p<0.001) difference indicating that COVID-19 had great consequences on the income. The regression result revealed that sex (p<0.001), marital status (p<0.010), household size (p<0.001), education (p<0.001) and experience (p<0.005) were feed mill profitability determining factors in the study area. Constraints faced during COVID-19 are that lockdown due to COVID-19 hindered operational activities of feed mill (65.26%), COVID-19 causes a total increase in the price of inputs (66.32), reduction in the sales of feeds (69.29%), reduction in work force (65.26%), and loss of raw materials through spoilage (66.32%). The study recommended that feed millers should collaborate with local farmers for the supply of materials at lesser price, rather than buying highcost foreign materials.